Resisting Imposed Identities in Postwar Fictions of the Self: Carmen Laforet's Nada (1945) and Rosa Chacel's Memorias de Leticia Valle (1945). - Lawlor, Hannie (Hispanic Research Journal, 2024)
The early years of the dictatorship saw a forceful attempt to restore the repressive nineteenth- and early-twentieth-century role of women in line with the social codes of Francoist Spain. The redesigning of the primary curriculum for girls, the revising of school textbooks, and the pervasive circulation of women's magazines became instruments in the reconstruction of a rigid and reductive model of female selfhood. At the same time as literature was co-opted by the regime in the re-imposition of this identity, however, it was mobilized by certain women writers as a space within which to resist it. This article explores first-person fictions of the self as a subversive strategy in the face of enforced identities, through a study of two texts published in 1945, one in Spain and the other in exile: Carmen Laforet's Nada and Rosa Chacel's Memorias de Leticia Valle. While in many ways very different, these texts share a powerful insistence on the complex and elusive identities of their female narrators, and on the agency these young women hold in articulating them. Foregrounding the power of the female voice and of self-characterization, they become sites of resistance to assumptions about women's identity, fixed power dynamics, and singular histories.